The Role of Motivation in The Google Workspace in The Tam Theory Implementation Education - Kusumaningrum, Indah; Joko Raharjo, Tri; Yulianto, Arief (Educational Management, 2022)
Through Davis's TAM theory, which was created in 1989, this study wants to find out how motivated people are to use the Google Workspace for Education (GWE) platform in blended learning as one of the media used in the independent curriculum. Actual System Usage, which measures user interest, is an internal variable. Perceived Ease of Use, Perceived Usefulness, Behavioral Intention to Use, and Motivation are all external factors. The study method is quantitative and descriptive, and path analysis is used to figure out how the different variables affect each other. There were 110 teachers from different schools who took part in this study's group. The results showed that the motivation variable directly had a significant positive effect on interest, and motivation also had a significant positive effect on respondents' attitudes toward using the Google Workspace for education platform for learning. Positive but not statistically significant results were found for the direct influence of convenience on interest and usability on interest, while the influence of usability, attitude, and convenience was able to mediate the influence of motivation, attitude, and convenience.